Optimizing Digital Potential: The Impact of ICT Literacy on the Success of Undergraduate Thesis Writing in the Information Age - Triyana, I Gusti Ngurah; I Made Candiasa; Dewa Gede Hendra Divayana; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2025)
Low levels of Information and Communication Technology (ICT) literacy among students hinder their ability to access, manage, and integrate digital information essential for thesis writing. This study aims to analyze the impact of ICT literacy on students' thesis writing ability. Employing a quantitative approach with an ex-post facto design, this study involved a sample of 162 alumni. Data were collected through a Likert scale questionnaire to measure ICT literacy and a thesis evaluation rubric to assess students' academic writing performance. Data analysis was conducted using Structural Equation Modeling (SEM) with LISREL 8.80 software, including normality testing, measurement model evaluation, and structural model analysis. The results indicate a significant and positive relationship between ICT literacy and students’ thesis writing ability (tvalue = 6.04 > 1.96; path coefficient = 0.53). The measurement model demonstrated valid indicators (standardized loading factor > 0.5) and reliable constructs (Composite Reliability > 0.7; Average Variance Extracted > 0.5). The technical, cognitive, and socio-emotional dimensions of digital literacy played a substantial role in enhancing students’ academic performance. The study concludes that ICT literacy is a key factor in the academic progress of final-year students, with important implications for the development of targeted digital literacy enhancement programs.